Pomalidomide with or without dexamethasone for relapsed/refractory multiple myeloma in Japan: a retrospective analysis by the Kansai Myeloma Forum - Matsumura-Kimoto, Yayoi; Kuroda, Junya; Kaneko, Hitomi; Kamitsuji, Yuri; Fuchida, Shin-ichi; Nakaya, Aya; Shibayama, Hirohiko; Uoshima, Nobuhiko; Yokota, Isao; Uchiyama, Hitoji; Yagi, Hideo; Kosugi, Satoru; et al. (International journal of hematology, 2018)
Determinants of the efficacy and safety of pomalidomide (POM) monotherapy or POM plus dexamethasone (DEX) (POM/DEX) for relapsed and refractory multiple myeloma (RRMM) were examined retrospectively in a real-world clinical practice setting in Japan. The subjects were 108 patients registered with the Kansai Myeloma Forum, who were treated with either POM or POM/DEX. Of these, 79 (73%), 73 (68%), and 58 (54%) were resistant to bortezomib (BTZ), lenalidomide (LEN), and both BTZ and LEN, respectively. The median overall survival (OS) was not reached. The median time to treatment failure (TTF) was 4.4 months. The best response was recorded in 96 patients, with a 31% overall response rate (ORR) and a 79% rate of achieving at least stable disease. Number of pre-POM regimens ≥ 5, non-IgG-type M-protein, and time from initial therapy to POM or POM/DEX therapy < 2 years were associated with shorter TTF and OS. Frequent (> 10%) severe adverse events included neutropenia (55.1%), thrombocytopenia (33.7%), anemia (30.6%), febrile neutropenia (12.2%), fatigue (11.2%), and anorexia (10.2%). In conclusion, POM and POM/DEX showed substantial efficacy against RRMM, but new combination therapies with POM are needed to improve efficacy further without causing hematologic toxicities.